Transforming growth factor-β receptors: versatile mechanisms of ligand activation - Chia Zheng-Jie; Cao Ying-nan; Little Peter J.; Kamato Danielle (Acta Pharmacologica Sinica, 2024)
Transforming growth factor-β (TGF-β) signaling is initiated by activation of transmembrane TGF-β receptors (TGFBR), which deploys Smad2/3 transcription factors to control cellular responses. Failure or dysregulation in the TGF-β signaling pathways leads to pathological conditions. TGF-β signaling is regulated at different levels along the pathways and begins with the liberation of TGF-β ligand from its latent form. The mechanisms of TGFBR activation display selectivity to cell types, agonists, and TGF-β isoforms, enabling precise control of TGF-β signals. In addition, the cell surface compartments used to release active TGF-β are surprisingly vibrant, using thrombospondins, integrins, matrix metalloproteinases and reactive oxygen species. The scope of TGFBR activation is further unfolded with the discovery of TGFBR activation initiated by other signaling pathways. The unique combination of mechanisms works in series to trigger TGFBR activation, which can be explored as therapeutic targets. This comprehensive review provides valuable insights into the diverse mechanisms underpinning TGFBR activation, shedding light on potential avenues for therapeutic exploration.